Pengaruh Persediaan Bahan Baku dan Tenaga Kerja terhadap Target Produksi - I Magi, Bahmid; Mulyadi, Diki (Ma'soem University, 2024)
The background of this study is fluctuations in production targets, due to the problem of raw material supply and labor at PT Tirta Gracia Semesta Mandiri, Bandung Regency which affects the production target. This research aims to determine the effect of raw material and labor supplies on production targets simultaneously and partially at PT Tirta Gracia Semesta Mandiri, Bandung Regency. Type of quantitative research using associative methods. The data used is primary data. Collection techniques through questionnaires, observations and interviews with employees of the companies studied. The population is all production employees at PT Tirta Gracia Semesta Mandiri, totaling 24 people with a sample of 24 people. Research results at PT Tirta Gracia Semesta Mandiri show that there is a significant influence between Raw Material Inventory on production targets of 14.5% for the R^2 test, with t test results where the t_count>t_table value (1.934 > 1.321) means that H_1 is accepted, there is a significant influence between Labor on Production Targets of 61.4% for the R^2 test, with t test results where the t_count > t_table value (5.917 > 1.321) means that H_1 is accepted, and simultaneously there is a significant influence between the supply of raw materials and labor on the production target of 61.8% for the R^2 test, with the F test results where the value of F_count > F_table (16.974 > 3 .44).